Angiotensin receptor neprilysin inhibitor LCZ696: pharmacology, pharmacokinetics and clinical development. (March 2017) - Hua, Yue; Wang, Ian; Liu, Bin; Kelly, Darren J; Reid, Christopher; Liew, Danny; Zhou, Yingchun; Wang, Bing H
Heart failure still has a significant disease burden with poor outcomes worldwide despite advances in therapy. The standard therapies have been focused on blockade of renin–angiotensin–aldosterone system with angiotensin-converting enzyme inhibitors, angiotensin receptor blockers and mineralocorticoid antagonists and the sympathetic nervous system with β-blockers. The natriuretic peptide system is a potential counter-regulatory system that promotes vasodilatation and natriuresis. Angiotensin receptor neprilysin inhibitors are a new class drug capable of blocking the renin–angiotensin–aldosterone system and enhancing the natriuretic peptide system to improve neurohormonal balance. The success of the PARADIGM-HF trial with LCZ696 and its approval for heart failure treatment is likely to generate a paradigm shift. This review summarises the current knowledge of LCZ696 with a focus on pharmacology, pharmacokinetics and pharmacodynamics, mechanisms of action, clinical efficacy and safety.